(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2018)
Background: Corporate Social Responsibility (CSR) refers to that part of business activities of an organization that have a positive impact on the society, environment and their surroundings at large. The concept of CSR is decade’s old but gained importance in 1990’s after the government made it mandatory for the organizations to contribute a part of their earnings to the society’s benefit. CSR in the Indian hospitality also gained importance at the same time when they realized that their customers, whether foreign or domestic are very much inclined to serve society in certain ways possible. They realized that people now-a-days do not just buy a product, they take up an initiative of the betterment of society as well and this motivates the Indian Hospitality to diversify the range and reach of their CSR initiatives and be called as ‘Socially Responsible Hospitality or Hotel Brand.’ Objective: The present study is done to understand CSR in terms of hospitality sector, to gain knowledge about CSR Initiatives taken up in the Hospitality sector: Hotels, and to know the awareness level of the employees for CSR activities working in perspective Hotels. Methodology: The details of the CSR Initiatives taken by the perspective hotels were taken by means of interview of the HR personnel of the organizations, Articles, Magazines, Previous Researches, Websites and Books. Questionnaires were filled up by the employees working in the organizations to check the employee awareness level regarding the CSR Initiatives taken up by their organization. Results: Details of the CSR Initiatives taken up by The Oberoi Maidens, ITC Maurya and The Leela Palace were arrived which indicated the members of CSR Committee of the hotel, initiatives taken up and their reach, target sectors of the initiatives and the budgetary support for the CSR Initiatives. Also, the awareness level of the employees was analyzed and summarized. Conclusion: CSR Initiatives, though a part of the hotel industry, need to be emphasized more as there is a misconception that the CSR Initiatives are taken by the hospitality industry for the publicity of their business.